O envolvimento do consumidor adolescente em relação ao risco percebido nas cirurgias plásticas estéticas - Miranda, Antônio Bruno Oliveira de (2007)
This dissertation planed to analyze the involvement of the adolescent consumer, faced by the perceived risk in his purchase decision process of the plastic surgeries aesthetic services in the city of Belém/PA. The relevance of this research gives for its applicability, to the enterprise area, therefore, will not only facilitate to one better agreement of doctors and hospital managers on the consuming importance of the adolescent public while the services of aesthetic plastic surgeries, as also, for the academy, since studies on the involvement in the country still sufficiently are reduced. The study it is associated with a quali-quantitative boarding of descriptive, exploratory and explicative nature. The research based itself on the main focus of the consumer s behavior, having as main focus his involvement in the purchase process, related to the perceived risk. This theoretical base, was used for the formularization of the research instrument in which was used with 80 (eighty) adolescent ones that they had been submitted to some type of aesthetic plastic surgery between January of 2005 and July of 2006. The research disclosed among others results, the high involvement of the adolescent with this type of service, as well as its satisfaction with the surgery.